In vitro culture and phylogenetic analysis of "Candidatus Arsenophonus triatominarum," an intracellular bacterium from the triatomine bug, Triatoma infestans - Hypsa, V; Dale, C (International journal of systematic bacteriology, 1997)
An intracellular symbiotic bacterium was isolated from the hemolymph of Triatoma infestans and cultured in an Aedes albopictus cell line. 16S ribosomal DNA sequence analysis revealed that the bacterium was a member of the gamma-3 subgroup of the class Proteobacteria, having 96.2% sequence identity with the most closely related bacterium, Arsenophonus nasoniae, the causative agent of the son-killer trait in the parasitoid wasp Nasonia vitripennis. These bacteria share morphological features and a common tissue distribution and transmission mode. The A. nasoniae-T. infestans symbiont branch represents a lineage of insect symbionts which may be capable of horizontal transmission between phylogenetically distant host insects. We propose that the intracellular symbiont from T. infestans be classified as "Candidatus Arsenophonus triatominarum." The bacterium found in the hemocytes of T. infestans is designated the type strain of this species.
Keywords: Symbiosis; Gram-Negative Bacteria; DNA bakterií; elektronová mikroskopie; RNA ribozomální 16S; Animals; DNA, Bacterial; Triatoma; symbióza; Microscopy, Electron; Phylogeny; zvířata; fylogeneze; gramnegativní bakterie; RNA, Ribosomal, 16S